Online Assessment of Islamic Religious Education Learning - Abdul Azis; Reem Abou-Samra; Andika Aprilianto (Tafkir: Interdisciplinary Journal of Islamic Education, 2022)
This article describes the planning and implementation of online-based exam evaluations in Islamic Religious Education Learning at the Nahdlatul Ulama 05 Brangsong High School. This article uses qualitative research with a case study approach. For data collection, researchers used observation, interviews, and documentation techniques. The results of this article are Planning for online-based assessment evaluation in Islamic Religious Education learning at SMA NU 05 Brangsong, (1) Planning in general (a) Preparation of school work programs, (b) Formation of an exam committee, (c) Preparing equipment both hardware and software. (2) Planning specifically, namely by (a) determining goals, (b) identifying student abilities, (c) compiling question grids and question cards, (d) making questions, (e) evaluation and analysis, (f) revision and creating new questions. Implementation of online-based exam evaluation in Islamic Religious Education learning at SMA NU 05 Brangsong, (1) implementation of pre-exams (2) Preparation and preparation of test schedules, (3) Division of test rooms, (4) Installing applications. Implementation of the assessment, (5) fill in the username and password, (6) do the questions, (7) end the test.